Integration of Classical Educational Thought into Modern Teaching: Lessons from ‘Ihya Uloom al-Deen’ and ‘Tadhkirat al-Sami’ wal-Mutakallim’ - K, Muhammed Harshad; KP, Hassan Shareef (Afkaruna: International Journal of Islamic Studies (AIJIS), 2025)
Contemporary education systems often struggle to create positive learning environments that foster holistic development, a challenge that may be addressed by examining classical pedagogical theories. This study investigates the potential integration of classical Islamic educational thought into modern teaching practices, specifically drawing from Imam Al-Ghazali's ‘Ihya Uloom al-Deen’ and Badr al-Din Ibn Jama’ah’s ‘Tadhkirat al-Sami’ wal-Mutakallim’, into modern teaching. Through qualitative content analysis, the research examines the educational principles presented in these texts to bridge the traditional and contemporary viewpoints. The study concentrates on teacher-student relationships, the art of teaching, and the teacher's classroom role. Key findings underscore the significance of compassion, ethical guidance, and spiritual growth in education. Effective teaching involves tailoring instruction to students' intellectual capacities, upholding personal dignity, and cultivating a positive learning atmosphere. The integration of these classical insights is posited to elevate modern education by fostering intellectual excellence and moral integrity.